2006
DOI: 10.2146/ajhp050460
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled anesthetic agents

Abstract: The inhaled anesthetics have been shown to be both safe and effective in inducing and maintaining anesthesia. These agents differ in potency, adverse-effect profile, and cost. Newer anesthetic gases, such as sevoflurane and desflurane, appear to have more favorable physico-chemical properties. These factors, as well as patient characteristics and duration and type of procedure, must be considered when selecting an inhaled anesthetic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 51 publications
1
43
0
Order By: Relevance
“…The following examples are not exhaustive, but show that sevoflurane may have properties that isoflurane does not, and vice versa. For example, the metabolism of sevoflurane (but not isoflurane) produces inorganic fluoride (Stachnik and Bonk, 2006), a molecule thought to cause nephrotoxicity, although one study on humans found no difference in renal function following prolonged anaesthesia with sevoflurane or isoflurane (Kharasch et al, 2001). Both isoflurane and sevoflurane cause physiological changes in rodents.…”
Section: First Exposurementioning
confidence: 99%
“…The following examples are not exhaustive, but show that sevoflurane may have properties that isoflurane does not, and vice versa. For example, the metabolism of sevoflurane (but not isoflurane) produces inorganic fluoride (Stachnik and Bonk, 2006), a molecule thought to cause nephrotoxicity, although one study on humans found no difference in renal function following prolonged anaesthesia with sevoflurane or isoflurane (Kharasch et al, 2001). Both isoflurane and sevoflurane cause physiological changes in rodents.…”
Section: First Exposurementioning
confidence: 99%
“…However, little is known regarding its comprehensive influence at the genomic and molecular levels, which is not reflected by mortality and morbidity. Sevoflurane is an inhalational anesthetic frequently used in Japan (4). It has low solubility in blood and tissues, thus there is usually a rapid recovery from anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…They are also important determinants of numerous pathological states and are the targets of therapeutic, as well as adverse actions, of clinically used pharmacological agents. Volatile general anaesthetics (VAs) induce safe and reversible loss of consciousness, enabling surgical procedures to be carried out (Stachnik, 2006;Bovill, 2008;Franks, 2008). Several membrane ion channels and receptors have been identified as targets of various VAs (Rudolph and Antkowiak, 2004;Hemmings et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Several membrane ion channels and receptors have been identified as targets of various VAs (Rudolph and Antkowiak, 2004;Hemmings et al, 2005). Enhancement of the activity of inhibitory ionotropic receptors (Lobo and Harris, 2005;Zeller et al, 2008), depression of the excitatory ionotropic receptors (Yamakura et al, 2001), potentiation of the 2P-domain K + channels (Patel and Honore, 2001), inhibition of voltage-gated Na + channels (Hemmings, 2009) and of the transient receptor potential (TRP) family member TRPC5 (Bahnasi et al, 2008) probably all contribute to the central clinically relevant anaesthetic effects, whereas the action of the same VAs on other ion channels might, at least in part, be responsible for their numerous adverse effects (Stachnik, 2006;Bovill, 2008). Indeed, activation of TRP member TRPA1 by the 'pungent' VAs (those that are known to excite peripheral nociceptive neurons), isoflurane and desflurane Cornett et al, 2008;Eilers et al, 2010), and sensitization of TRPV1 to its agonists, capsaicin and protons Eilers et al, 2010), might contribute to postoperative pain and inflammation, as well as producing airway irritation.…”
Section: Introductionmentioning
confidence: 99%